USING THE DISCUSSION BOARD DURING YOUR ONLINE SYNCHRONOUS CLASS TO ENGAGE STUDENTS. Issue 2 (3rd April 2022) - Cooper, Alicia D.
ABSTRACT: Educators constantly wrestle with the question of how to engage students in an environment in which students are increasingly distracted. This issue has become more relevant as instructors have been forced to pivot to the use of a variety of online learning modalities to administer instruction. While the synchronous online class session allows for the safe delivery of instruction, it also makes it difficult to engage an entire class of students during the session. The current article proposes the synchronous use of the online discussion board during the class session as a mechanism for enhancing student engagement. This innovation was selected for the 2021 Wessex Press Innovations in Teaching Award.